QUALITY OF SERVICES IN MAKING CHILD IDENTITY CARD AT THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION - Gibra Septa (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The background for doing this research is because the implementation of Child Identity Card (KIA) at the Cirebon Regency Population and Civil Registration Service is still not optimal. This study uses a qualitative descriptive method with in-depth interviews, direct observation, literature study. The sampling technique used purposive sampling through interviews with key information from the Head of the Population Registration Service and the Population Identity Section of the Cirebon Regency Population and Civil Registration Office and supporting informants, namely the community who provided Child Identity Card (KIA) services at the Cirebon Regency Population and Civil Registration Service. The technique of testing the validity of the data used in the research is the triangulation technique. The data analysis technique used in this research is by means of data reduction, data presentation and verification. The results tangibel seen from the appearance of officers/apparatus in serving customers is optimal because it is in accordance with the provisions of the use of official uniforms, but the convenience of the place to perform services and the ease of service in the service process is not optimal because the waiting room is not comfortable and the numbers are not regular.